2017
DOI: 10.1080/17470218.2016.1161058
|View full text |Cite
|
Sign up to set email alerts
|

Do People Have Insight into their Face Recognition Abilities?

Abstract: Diagnosis of developmental or congenital prosopagnosia (CP) involves self-report of everyday face recognition difficulties, which are corroborated with poor performance on behavioural tests. This approach requires accurate self-evaluation. We examine the extent to which typical adults have insight into their face recognition abilities across four experiments involving nearly 300 participants. The experiments used five tests of face recognition ability: two that tap into the ability to learn and recognize previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 65 publications
10
92
0
1
Order By: Relevance
“…asking participants to rate their face recognition ability ‘compared with the average person’) may not be a fruitful approach [19]. Nevertheless, we note that self-report scores elicited using abstract one-shot measures do correlate significantly with objective measures of face recognition ability [24,25,28]. Individuals with extremely good or extremely bad face recognition ability (so-called ‘super-recognizers’ [29] and DPs, respectively) are also more likely to encounter situations in their daily lives which illustrate that face recognition is a distributed ability, and suggest where they might fall within that distribution.…”
Section: Discussionmentioning
confidence: 99%
“…asking participants to rate their face recognition ability ‘compared with the average person’) may not be a fruitful approach [19]. Nevertheless, we note that self-report scores elicited using abstract one-shot measures do correlate significantly with objective measures of face recognition ability [24,25,28]. Individuals with extremely good or extremely bad face recognition ability (so-called ‘super-recognizers’ [29] and DPs, respectively) are also more likely to encounter situations in their daily lives which illustrate that face recognition is a distributed ability, and suggest where they might fall within that distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging, for example with voxel-based morphometry, could be used to determine whether individual differences observed here are reflected in face-sensitive cortical areas (Bukach et al, 2012), which are also recruited when people draw simple cartoon faces (Miall, Gowen, & Tchalenko, 2009). Our findings also point to a potential use for portrait drawing tasks in applied settings (i.e., forensic or recruitment situations in which good face processing skills are desirable) as an additional marker of skills, since people have poor insight into their face processing abilities (Palermo et al, 2017). To that end, future research might develop more automatic measures of faithfulness, for example algorithms that compute deviations between drawings and the model, instead of subjective ratings that might be more challenging to obtain.…”
Section: Discussionmentioning
confidence: 93%
“…Davis and colleagues suggested that prosopagnosia could be either developmental or acquired as a consequence of specific cortical neuronal damage (3,4). Overall, exploitation of super-recognizers is invaluable, particularly in lawenforcement and intelligence agencies (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals are the exact opposite of people with a medical condition, known as "prosopagnosia" or "face blindness". In this condition, an individual has deteriorated or limited abilities to recognise faces (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%